The association between prenatal exposure and childhood asthma: the mediating role of gut microbiota - Ning, Zidi; Zhang, Ye; Lu, Ruoyu; Zhao, Anda; Wang, Zeyu; Yuan, Jiajun; Li, Shenghui (Frontiers in Microbiology, 2025)
BackgroundAsthma is a common chronic respiratory disease that usually originates in early childhood. Emerging evidence implicates the gut microbiota as a modulator in asthma development, with growing attention to the interplay between prenatal exposures, maternal/offspring gut microbiota, and subsequent asthma risk. However, no comprehensive review has systematically examined the relationships.ObjectiveThis review aimed to explore whether the gut microbiota acts as a mediating factor in the association between prenatal exposure and childhood asthma.ResultsA systematic search was performed in the PubMed, Scopus, and Web of Science databases up to March 1, 2025, employing keywords related to childhood asthma, gut microbiota, and prenatal exposure. Only population-based studies were considered. Eight studies met the inclusion criteria. Among which, two focused on pet exposure during pregnancy, three on delivery mode, two on the combined effects of delivery mode and antibiotic exposure, and one on maternal diet. Exposure to pets during pregnancy may result in distinct microbiota profiles in the offspring, which may potentially confer a protective effect against asthma. Antibiotic use and cesarean delivery were associated with increased asthma risk. Conversely, high maternal fecal short-chain fatty acid levels appeared protective against childhood asthma development. The gut microbiota may play a mediating role in these associations.ConclusionPrenatal factors significantly correlate with offspring gut microbiota and early immune development, thereby affecting asthma susceptibility. Further studies are needed to expand prenatal exposure assessments and elucidate the specific mechanisms by which the gut microbiota mediates the association between prenatal exposures and childhood asthma.